2022
DOI: 10.1093/geront/gnac157
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Implementation Strategies Using the CFIR-ERIC Matching Tool to Mitigate Barriers in a Primary Care Model for Older Veterans

Abstract: Background and Objectives As the proportion of the U.S. population over 65 and living with complex chronic conditions grows, understanding how to strengthen the implementation of age-sensitive primary care models for older adults, such as the Veterans Health Administration’s Geriatric Patient-Aligned Care Teams (GeriPACT), is critical. However, little is known about which implementation strategies can best help to mitigate barriers to adopting these models. We aimed to identify barriers to Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These include conduct of on-going trainings, educational meetings among AHD providers and developing educational materials such as posters and guidelines as references for staff with inadequate knowledge to use during screening [15,30]. These strategies are well cited in other implementation research and interventional studies [15,32]. Continuous training leads to improved provider's self-con dence, uniformity and consistent quality of work through adherence to policy guidelines supporting the interventional programme [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include conduct of on-going trainings, educational meetings among AHD providers and developing educational materials such as posters and guidelines as references for staff with inadequate knowledge to use during screening [15,30]. These strategies are well cited in other implementation research and interventional studies [15,32]. Continuous training leads to improved provider's self-con dence, uniformity and consistent quality of work through adherence to policy guidelines supporting the interventional programme [20].…”
Section: Discussionmentioning
confidence: 99%
“…It was developed through input from 169 implementation science experts, who selected and ranked up to seven of the 73 ERIC strategies they thought would best address each CFIR barrier [30]. The CFIR-ERIC Matching tool was developed as a way to link these two key resources to help users understand which ERIC implementation strategies will best address CFIR related barriers [32] Study setting…”
Section: Research Frame-work Toolmentioning
confidence: 99%
“…Specifically, we used the CFIR-ERIC matching tool to identify strategies that addressed barriers to implementation that were identified by our Research Advisory Board. Other studies have demonstrated the usefulness of the CFIR-ERIC matching tool ( Shin et al, 2022 ; Weir et al, 2021 ), although the extent to which this tool generates the most effective and comprehensive set of implementation strategies warrants additional testing. In our work, we complemented our use of the CFIR-ERIC matching tool with an activity log to capture strategies used in real time.…”
Section: Discussionmentioning
confidence: 99%
“…For each strategy, the tool provides the percentage of experts who ranked that particular strategy in their top seven. This percentage can be interpreted at two levels of endorsed strategies, namely, Level 1 endorsed ERIC strategies (i.e., more than 50% of the experts ranked this as one of their top seven strategies for that barrier) and Level 2 endorsed ERIC strategies (i.e., between 20% and 50% of the experts ranked this as one of their top seven strategies for that barrier) ( 5 , 23 ). The research group determined that, for the continuation of this study, the top three strategies with the highest agreement or three strategies with an agreement higher than 50% would be used.…”
Section: Methodsmentioning
confidence: 99%